Meningkatkan Reading Comprehension Skills Melalui Pendekatan Whole Language Pada Siswa Menengah Pertama - Haerunnisa, Haerunnisa (STKIP Taman Siswa Bima, 2024)
This study explores the implementation of the Whole Language approach to enhance Reading Comprehension Skills among middle school students at SMPN I Bolo. Facing significant challenges in mastering comprehensive language skills, this research utilized a Classroom Action Research method conducted in two cycles, integrating interactive and holistic language learning activities. Initial observations showed that only 61.2% of students achieved the expected level of comprehension, which triggered the need for an integrated approach in teaching. Subsequent adjustments resulted in a substantial increase in comprehension levels, with 91.7% of students achieving the target comprehension scores in the second cycle. The findings indicate that the Whole Language approach not only improves reading comprehension but also actively involves students in the learning process through guided reading and writing activities. This study confirms the effectiveness of the Whole Language approach in creating an engaging and comprehensive learning environment, significantly enhancing students’ reading comprehension abilities.